Immunogenicity and safety of the Haemophilus influenzae type b and Neisseria meningitidis serogroups C and Y-tetanus toxoid conjugate vaccine co-administered with human rotavirus, hepatitis A and 13-valent pneumococcal conjugate vaccines: results from a phase III, randomized, multicenter study in infants - Nicola P. Klein; Remon Abu-Elyazeed; Yaela Baine; Brigitte Cheuvart; Marcela Silerova; Narcisa Mesaros (Taylor & Francis Group, 2019)
This phase III, open-label, randomized study (NCT01978093) evaluated the immunogenicity and safety of co-administered Haemophilus influenzae type b-Neisseria meningitidis serogroups C and Y-tetanus toxoid conjugate vaccine (Hib-MenCY-TT) with human rotavirus vaccine (HRV), hepatitis A vaccine (HAV) and 13-valent pneumococcal conjugate vaccine (PCV13). We randomized 600 infants (1:1) to receive 4 doses of Hib-MenCY-TT at 2, 4, 6 and 12-15 months of age or 3 doses of Hib vaccine conjugated to N. meningitidis outer membrane protein complex (Hib-OMP) at 2, 4 and 12-15 months of age. All infants received HRV at 2 and 4 months of age, PCV13 at 2, 4, 6 and 12-15 months of age, HAV at 12-15 and 18-21 months of age, and diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliovirus vaccine at 2, 4 and 6 months of age. We measured immune responses against HRV, HAV and Hib with enzyme-linked immunosorbent assays, and against MenC/MenY with serum bactericidal assays using human complement. The 4-dose vaccination series with Hib-MenCY-TT induced a robust immune response against Hib, which was non-inferior to that induced by a 3-dose vaccination series with Hib-OMP, and against MenC and MenY. Hib-MenCY-TT did not interfere with immune responses to concomitantly administered HRV, PCV13 and HAV. We did not identify any safety concern. In conclusion, we showed that 4-dose vaccination series with Hib-MenCY-TT during infancy did not interfere with immune responses of co-administered HRV, PCV13 and HAV, induced robust immune responses against Hib, MenC and MenY, and had a clinically acceptable safety profile.